Proses Endforming dan Bending Fuel Tube pada PT. XYZ - Gymnastiar, Dimas Faatihah; Yuliana Suryani, Intan; Okta Prianzo, Ivan; Putri Nabila, Zahwa (DPPM UNIVERSITAS PELITA BANGSA, 2023)
This research analyzes the endforming and bending process of fuel tubes at PT XYZ, an automotive component manufacturing company. The main objective of this study was to provide a comprehensive overview of the key stages in the manufacturing process, the efficiency of machine utilization, and the quality control system implemented. Data was collected through direct observation, interviews with production staff, and analysis of company documents. The results show that PT XYZ has successfully implemented advanced technology and a strict quality control system to improve efficiency and product quality. The efficient and well-controlled manufacturing process has helped the company in maintaining its position as a market leader in the automotive industry. Recommendations include the development of new technologies, continuous training for staff, evaluation of the quality control system, and increased collaboration with raw material suppliers. Hopefully, the findings of this study can serve as a reference for other companies in the automotive industry to optimize their manufacturing processes.